PENGARUH KELENGKAPAN PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA BABY SHOP ROBERTO SUMBAWA: Indonesia - Melisa Melisa; Muhammad Nur Fietroh (Journal of Management and Business, 2021)
This study aims to determine the effect of Product Completeness, Service Quality and Price on purchasing decisions at the Kids and Baby Shop Roberto Sumbawa. This study uses quantitative methods. The sample in this study amounted to 100 respondents obtained by purposive sampling. The data obtained were processed using data analysis techniques consisting of Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Testing and Coefficient of Determination Test through Software Statistical Package for the Social Science (SPSS) version 16.0. The results of the analysis in this study indicate that (1) the completeness of the product does not affect the purchase decision of Roberto Sumbawa's Kids and Baby Shop. (2) Quality of Service influence on purchasing decisions for Kids and Baby Shop Roberto Sumbawa and Price have an influence on purchasing decisions for Kids and Baby Shop Roberto Sumbawa.